2017
DOI: 10.1177/0033294117726288
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Adult Attachment Anxiety on Deception Judgments: Examining the Moderating Effect of Motivation

Abstract: Several psychologists have paid attention to individual differences in deception detection, but only a few studies have found significant results. The present study aimed to explore the relationship between attachment anxiety and deception judgment when there are no obvious cues to distinguish lies from truth, and to examine the moderating effect of motives. Participants were instructed to judge each of 10 audios on whether they were true or false. Subsequently, the attachment anxiety of participants was asses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 22 publications
(40 reference statements)
0
2
1
Order By: Relevance
“…Previous studies also found that participants engaging in unconscious process were more likely to use non-verbal/paraverbal cues, which in turn led to higher accuracy (Feeley and Young, 2000; Reinhard et al., 2013). By contrast, previous studies found that more deliberate processes caused by higher motivation led to higher detection accuracy if participants focused on and processed verbal rather than non-verbal cues (Reinhard, 2010; Reinhard and Sporer, 2010; Wu et al., 2018). It is suggested that verbal cues, rather than non-verbal/paraverbal cues, are more effective for the conscious process.…”
Section: Discussioncontrasting
confidence: 64%
See 1 more Smart Citation
“…Previous studies also found that participants engaging in unconscious process were more likely to use non-verbal/paraverbal cues, which in turn led to higher accuracy (Feeley and Young, 2000; Reinhard et al., 2013). By contrast, previous studies found that more deliberate processes caused by higher motivation led to higher detection accuracy if participants focused on and processed verbal rather than non-verbal cues (Reinhard, 2010; Reinhard and Sporer, 2010; Wu et al., 2018). It is suggested that verbal cues, rather than non-verbal/paraverbal cues, are more effective for the conscious process.…”
Section: Discussioncontrasting
confidence: 64%
“…Second, no personality factors were considered in the present study. However, a previous study found that attachment anxiety interacted with motivation in a deception detection task (Wu et al., 2018). This suggested that individuals with different personality traits might perform differently when they use conscious or unconscious processes to detect deception.…”
Section: Discussionmentioning
confidence: 94%
“…We broaden the existing knowledge by demonstrating how (1) workplace ostracism or employees' sense of exclusion operates as a critical mechanism that links perception of contract breach with counterproductive work behaviors, and (2) the role of attachment anxiety in reinforcing this process. In this way, our results focus on the direct beneficial effect of employees' attachment anxiety on work outcomes, such as deception judgments (S. Wu, Cai, et al, 2018), relational opportunities, negative emotions (Paech et al, 2016), and relationship threats. Moreover, we show that the benefits of attachment anxiety may even be indirect , such that employees who yearn for closeness and acceptance, but harbor deep‐seated fears of rejection, are in a worse position to tackle an unfavorable work condition such as perceived contract breach.…”
Section: Discussionmentioning
confidence: 99%